Stereoselective synthesis of novel tubulin inhibitors with diverse functionality for integration into molecular conjugates and designed multiple ligands - Stack, Gary (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
The principal objective of the work described in this thesis was the synthesis of a series of novel tubulin inhibitors, with defined stereochemistry and diverse functionality, suitable for the formation of molecular conjugates and designed multiple ligands. It was envisaged that these compounds would permit the synthesis of molecular conjugates via a wide variety of coupling methodologies, while retaining the tubulin inhibitor activity of the core structure. Furthermore, the design, synthesis and evaluation of a designed multiple ligand possessing both tubulin polymerisation and aminopeptidase N inhibition activity was proposed.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin